Improving Students’ Score in the General Aptitude Test with Test Repetition without the Need of Professional Training - Al-Johani, Mohammad Saleh; Al-Subaihi, Ali Ahmad (Journal of Educational and Psychological Sciences, 2021)
This study aimed to identify the extent to which students’ score on the General Aptitude Test (GAT) improved when taking the test more than once. The semi-experimental approach was applied for its relevance to the objectives of the current study to follow up on the experience of repeating the GAT several times by the target students. The study sample consisted of (40) high school students who took the GAT (once, twice, three times, four times). The results of the study showed statistically significant differences between students’ scores on the GAT according to the difference in the number of times they took the test; the students’ score improved when they took the test more than once. Besides, the study showed that there were no statistically significant differences at the level of significance (0.05) between the average score on the GAT in the second time and the average score in the third time; there is no improvement in their grades the third time compared to their scores the second time. The study recommended educating students to take the test more than once, in order to achieve the best possible result. The study concluded that taking the test more than once has positive effects on the student and their families and mitigate worrying about the process of repeating the test. Finally, in light of the results, the study suggested conducting some studies with the aim to investigate the students’ reluctance to repeat the test four times and a study to identify the forms of professional training necessary for students to test and study the training’s impact on students’ psychology and their future aspirations.